PERAN KOMITE MADRASAH DALAM MENINGKATKAN MUTU MADRASAH DI MADRASAH IBTIDAIYAH NAHDLATUL ULAMA POLOWIJEN - Lailatul Choyriah; Rosichin Mansur; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Abstract            This research is based on the role of the madrasa committee in improving madrasa quality in the Madrasah Ibtidaiyah Nahdlatul Ulama Polowijen Malang, in carrying out its role as a provider of considerations, supporters, controllers, and liaison because it has not fully understood the committee's role itself. The purpose of this study is to describe, analyze and concludethe work program of the madrasa committee, the role of the madrasa committee, and the supporting and inhibiting factors of the role of the madrasa committee in improving madrasa quality in the Madrasah Ibtidaiyah Nahdlatul Ulama Polowijen Malang. This research uses a qualitative approach and type of case study research...Data collection uses observation, interviews and documentation. Entering data analysis techniques using data condensation, data presentation and conclusion drawing. The results of this study are the role of the madrasa committee in giving consideration to the supporters, controllers and liaison applied in the madrasa committee work program as well as the supporting and inhibiting factors of the madrasa committee's role. Supporting factors and obstacles to the role of the committee exist internal factors, namely the committee itself and an understanding of the roles and functions of the committee. While external factors that correlate with this and support from the education office and the management of the madrasa.Keywords: Role of the Committee, Improving Quality